The cost-effectiveness of using latrine dehydrated and pasteurization pellets and struvite: Experimental evidence from South Africa. Issue 4 (7th June 2018) - Chapeyama, Benjamin; Wale, Edilegnaw; Odindo, Alfred
Abstract : Faecal sludge and urine can be recycled and processed into usable fertilizer products such as the latrine dehydrated and pasteurization ('LaDePa') pellets and struvite, respectively. To quantitatively determine the financial cost effectiveness of using LaDePa and struvite, a study was conducted using experimental data for maize, wheat and sugarcane production in KwaZulu-Natal, South Africa. The costs per hectare of using these potentially new human waste-based fertilizer products to meet crop nutrient requirements for the selected crops and achieve the optimum target yields were determined and compared with the costs per hectare of using recommended commercial fertilizers. The financial feasibility was determined using partial budgets. The results showed that both LaDePa and struvite are financially viable if used in place of the organic fertilizer studied. LaDePa is even more cost effective if it is used as a soil amendment to improve soil physical properties.